First report of pod and stem blight of Lima bean caused by Diaporthe phaseolorum var. sojae in Malaysia. - Mahmodi, F.; Kadir, Jugah; Puteh, Adam; Wong, Mui Yun; Nasehi, A. (American Phytopathological Society, 2013)
In July 2011, a severe outbreak of pod and stem blight was observed on lima bean (Phaseolus lunatus) plants grown in the Cameron Highlands, located in Pahang State, Malaysia. Disease incidence varied from 33 to 75% in different fields. Pods and stems exhibited withered, light brown to reddish brown necrotic areas. Sub-circular and brown lesions were produced on the leaves. These lesions varied in size, often reaching a diameter of 1 to 2 cm. After tissue death, numerous pycnidia were observed on the surface of the pod or stem. Based on morphological characteristics, sequence analysis of the rDNA internal transcribed spacer region, and pathogenicity test, the causal agent was identified as D. phaseolorum var. sojae. This is thought to be the first report of D. phaseolorum var. sojae causing pod and stem blight of lima bean in Malaysia.